Data set on the influence of members of a couple on family vacation decision-making - Rojas-de-Gracia, María Mercedes; Alarcón-Urbistondo, María del Pilar; Casado-Molina, Ana María (Elsevier, 2019)
This article describes a database on the perceptions of members of a couple regarding the influence exerted in three stages and seven sub-decisions in the family vacation decision-making process. We obtained responses from 375 couples, whose members each completed the questionnaire individually, which also enables researchers to obtain information about the consensus between the perceptions of both regarding said influence. To complement this information, we also included sociodemographic and travel behavior variables for the couples analyzed. The data are publicly available at https://github.com/mmrojasgracia/Data-in-Brief_Influence. For interpretation and discussion, please see the original article entitled “Is asking only one member of a couple sufficient to determine who influences tourism decisions?” (Rojas-de-Gracia et al., 2019). - Este artículo aborda una base de datos sobre las percepciones que los miembros de una pareja tienen sobre la influencia que se ejercen en tres etapas (inicio, búsqueda y decisión final) y siete subdecisiones (destino, alojamiento, transporte, presupuesto, fecha, actividades, restaurantes) en el proceso de toma de decisiones de vacaciones familiares. Se recogen respuestas de 375 parejas, cuyos miembros completaron el cuestionario de forma individual, lo que permite además obtener información sobre el consenso entre las percepciones de ambos sobre dicha influencia. Para complementar esta información, se incluyeron también variables sociodemográficas y de comportamiento de viaje de las parejas analizadas. Los datos están disponibles públicamente en https://github.com/mmrojasgracia/Data-in-Brief_Influence. Para su interpretación y discusión, véase el artículo original titulado “Is asking only one member of a couple sufficient to determine who influences tourism decisions?” (Rojas-de-Gracia et al., 2019).
Keywords: Familia - Toma de decisiones; Roles de pareja; Toma de decisiones familiares; Consenso diádico; Influencia percibida de la pareja; Vacaciones familiares; Couple roles; Family decision-making; Influence of the couple; Family vacations; Perceived partner influence; Response agreement; Dyadic consensus